Skrining Covid-19 Menggunakan Rapid Diagnostik Test (RDT) Pada Masyarakat RT 30 Kelurahan Air Hitam - Harianja, Edison; Marsudi, La Ode (Jurnal Pengabdian Masyarakat Teknologi Laboratorium Medik Borneo, 2022)
Coronavirus is a collection of viruses that can infect the respiratory system. In most cases, this virus only causes mild respiratory infections, such as the flu. However, this virus can also cause severe respiratory infections, such as lung infections (pneumonia), Middle-East Respiratory Syndrome (MERS), and Severe Acute Respiratory Syndrome (SARS). The high rate of transmission in Indonesia makes every region always urge the public to implement health protocols and reduce activities outside the home. In handling the Covid-19 case, fast diagnostic enforcement is needed to determine the next step. One of the tools to assist in the diagnosis of Covid-19 is a supporting examination. The supporting tests in the laboratory currently available are PCR swabs and rapid tests. There are two types of rapid tests for Covid-19, namely antigen detection and antibody detection against the SARS-CoV-2 virus which causes Covid-19. This community service activity aims to assess the development of the Covid-19 case, it is necessary to carry out early detection in the community in the Air Hitam subdistrict RT 30, by carrying out a Covid-19 screening test using the Rapid Diagnostic Test (RDT).